120 W Efficient Single Frequency Amplification Based on Wide Tunable 1018 nm DBR Seed Source - Pan Li; Linfeng Li; Kaiming Cao; Ruihong Gao; Heshan Liu; Meng Shi; Ziren Luo (IEEE Photonics Journal)
High-power, widely tunable 1018 nm single-frequency fiber lasers and their harmonics play a crucial role in Rydberg microwave measurement applications. This study focuses on the development of a high-power 1018 nm single-frequency narrow-linewidth fiber laser amplifier based on a DBR single-frequency seed source. The DBR seed source, constructed using an 8 mm-long doped fiber, achieves a linewidth of 3.25 kHz and demonstrates a wavelength tuning range exceeding 1.51 nm across a temperature range of −10 $^{° }$ C to 120 $^{° }$ C. The tuning process exhibits excellent linearity between wavelength and temperature, with no observed mode hopping. To ensure high ASE and SBS suppression in the amplified output, a four-stage amplification and filtering scheme was implemented. By carefully selecting optical fibers and optimizing their lengths, the system achieves an output power exceeding 120 W for the 1018 nm single-frequency laser. Experimental results demonstrate a light-to-light conversion efficiency of over 77% in the main amplification stage, with an ASE suppression ratio greater than 60 dB. The amplified laser exhibits an output linewidth of 10.3 kHz and maintains exceptional beam quality, with an M $^{2}$ factor of less than 1.3. These results highlight the effectiveness of the proposed design for high-power, narrow-linewidth laser applications.